P 126 Congruence of first out-patient routine EEG and in-patient EEG diagnostics in a specialized epilepsy center. Issue 10 (October 2017) - Steinhoff, B.; Bacher, M.; Intravooth, T.; Stockinger, J.; Staack, A.
Abstract : Background/Objective: In our epilepsy center we always perform a routine EEG in out-patients who are referred for the first time. We investigated in how many cases additional EEG diagnostics including long-term video EEG delivered additional clinically relevant information if in-patient diagnostics followed. Methods: We retrospectively assessed, how many out-patients seen for the first time were admitted to a hospital stay. In these cases we compared the EEG findings of the initial out-patient routine EEG with the in-patient data including long-term video EEG. Results: Total number of out-patients was 77. Ten patients (13%) were hospitalized with the purpose of a better diagnostic classification. In 4 of 10 epilepsy cases we found confirming epileptiform discharges in the long-term video EEG that had not been recording with the initial routine EEG. In one patient we found a normal variant where epileptiform discharges had been falsely supposed in the routine EEG. In the remaining cases no clinically relevant further information was obtained. Discussion/Conclusions: Additional hospitalizations are usually not necessary after out-patient visits of new referrals to a specialized epilepsy center. In half of these hospitalized patients additional EEG diagnostics beyond routine EEG render clinically relevant additional information.